1992
DOI: 10.1111/j.1365-2982.1992.tb00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic motor patterns of phase II and behaviour of phase III in the fed state

Abstract: The motor pattern of the phase I1 of the migration motor complex ( M M C ) is poorly characterized and it remains t o be determined whether it differs from the fed motor-pattern. Furthermore, discrepancy exists on the disruption of ongoing M M C s b y feeding, and finally, the understanding of the behaviour of phase IIIs during enteral nutrition is incomplete. Therefore, canine intestinal motility was studied after meal and during enteral infusion o f nutrients (elemental diet, glucose, maltose, amino acids) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…The MMC continues in spite of ingestion of food by a horse on an ad libitum basis (i.e. grazing), which is similar to that seen in ruminants, in contrast to a post cibum switch to a 'fed pattern'essentially a prolonged Phase 11that is seen in carnivora and primates that basically meal feed (Ruckebusch and Bueno 1976;Siegle and Ehrlein 1988;Ehrlein et al 1992). It is during Phase &like activity, not during Phase 111, that most of the transit of intestinal contents occurs (Ruckebusch and Fioramonti 1975;Summers and Dusdieker 1981;Memtt and Ruckebusch 1988).…”
Section: Integrated Duodenal Myoelectrical Activity In a Fasted Horsementioning
confidence: 61%
“…The MMC continues in spite of ingestion of food by a horse on an ad libitum basis (i.e. grazing), which is similar to that seen in ruminants, in contrast to a post cibum switch to a 'fed pattern'essentially a prolonged Phase 11that is seen in carnivora and primates that basically meal feed (Ruckebusch and Bueno 1976;Siegle and Ehrlein 1988;Ehrlein et al 1992). It is during Phase &like activity, not during Phase 111, that most of the transit of intestinal contents occurs (Ruckebusch and Fioramonti 1975;Summers and Dusdieker 1981;Memtt and Ruckebusch 1988).…”
Section: Integrated Duodenal Myoelectrical Activity In a Fasted Horsementioning
confidence: 61%
“…Nutrients may have different effects on small intestinal motility depending on the physiologic activity at the moment the stimulus is applied: if nutrients are administered during phase I of the MMC, an expected fed pattern of irregular contractions has been observed, but if the same nutrients are instilled during late phase II, fasting activity remains unmodified [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in dogs showed that enteral nutrient infusion of more than 0.5 kcal min −1 converts cyclical fasting activity into a so‐called postprandial pattern, until at rates of approximately 4 kcal min −1 conversion will always be triggered 3,18 . Our results demonstrate that in humans, energy loads of 1.32–3.96 kcal min −1 , lying within physiologic range of gastric emptying, always initiate such a motor response.…”
Section: Discussionmentioning
confidence: 53%